2021
DOI: 10.1155/2021/1102297
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Double V-Rings in the Heat Exchanger Duct on Heat Transfer and Flow Behaviors: A Numerical Study

Abstract: The impacts of the double V-rings (DVR) in the heat exchanger duct (HED) on heat transfer and flow structures are numerically analyzed. The general configuration of the DVR is called “type I,” while the discrete DVR can be split into two structures, which are called “types II and III.” The influences of the DVR sizes, DVR types and flow directions on heat transfer rate, friction loss, and thermohydraulic performance are considered. The Reynolds numbers in the range around 100–2000 (laminar regime at the entran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The present numerical method is referred from Ref. (Boonloi and Jedsadaratanachai (2021a) and Jedsadaratanachai and Boonloi (2014)).…”
Section: Mathematical Foundation Boundary and Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present numerical method is referred from Ref. (Boonloi and Jedsadaratanachai (2021a) and Jedsadaratanachai and Boonloi (2014)).…”
Section: Mathematical Foundation Boundary and Initial Conditionsmentioning
confidence: 99%
“…They found that the best SAH performance of their investigated range is around 1.89. Moreover, Boonloi and Jedsadaratanachai (2021a) and Jedsadaratanachai and Boonloi (2014) improved the heat exchanger performance with double V-shaped vortex generators. They found that the double V-shaped vortex generators provided high effectiveness to improve heat-exchanger performance.…”
Section: Introductionmentioning
confidence: 99%